Recycling of Polyethylene Terephthalate - Forrest, Martin J. (De Gruyter, 2019)
Polyethylene terephthalate (PET) is the most recycled plastic in the world. This book covers all from the world market of PET to the many technologies and processes developed for separation, decontamination, recycling and manufacturing into food-grade and non-food-grade products of PET. Also, regulations, testing methods and analytical procedures according to the current regulatory framework are presented.- Resumé vydavatel
Keywords: polyethylentereftalát; recyklace plastů; termoplasty; polyethylene terephthalate; plastics recycling; thermoplastics; elektronické knihy; monografie; electronic books; monographs